Comparing impeller performance for solid-suspension in the transitional flow regime with Newtonian fluids - Ibrahim, Shaliza; Nienow, A.W. (Elsevier, 1999)
Particle suspension in Newtonian fluids of viscosities from 0.01 to 1 Pa s have been studied using Rushton turbines, pitched blade turbines, Chemineer HE-3 and Lightnin' A310 hydrofoils (all pumping downwards), and Ekato Intermig agitators. By comparison to the turbulent system (Ibrahim and Nienow, 1996), at high viscosity, there was less random particle movement across the base prior to suspension. On the other hand, once the agitation speed, N, was high enough to achieve suspension, i.e., N = N(js), particles remained longer in suspension after a reduction to N < N(js), though eventually with little or no hysterisis. Suspension at high viscosity was achieved with a lower mean specific energy dissipation rate, (Îµ(T))(js), when using large D/T impellers whether of the radial or axial type. Thus, at Re > 3000, the optimum overall configuration was a D/T of about 0.4 with the downward pumping HE-3 and pitched blade turbines, whilst at Re < 3000, the optimimum was the HE-3 at a D/T of about 0.5. The performance of dual Intermigs with D/T ratios of ~0.6 dramatically improved as the viscosity increased to 0.1 Pa s, and the single Intermig was the most efficient impeller at 1 Pa s. The Zwietering equation was found unsuitable for prediction of N(js) at low Re. Particle suspension in Newtonian fluids of viscosities from 0.01 to 1 Pa s have been studied using Rushton turbines, pitched blade turbines, Chemineer HE-3 and Lightnin' A310 hydrofoils (all pumping downwards), and Ekato Intermig agitators. By comparison to the turbulent system, at high viscosity, there was less random particle movement across the base prior to suspension. On the other hand, once the agitation speed, N, was high enough to achieve suspension, i.e., N = Njs, particles remained longer in suspension after a reduction to N<Njs, though eventually with little or no hysterisis. Suspension at high viscosity was achieved with a lower mean specific energy dissipation rate, (ÎµT)js, when using large D/T impellers whether of the radial or axial type. Thus, at Re>3000, the optimum overall configuration was a D/T of about 0.4 with the downward pumping HE-3 and pitched blade turbines, whilst at Re<3000, the optimimum was the HE-3 at a D/T of about 0.5. The performance of dual Intermigs with D/T ratios of approximately 0.6 dramatically improved as the viscosity increased to 0.1 Pa s, and the single Intermig was the most efficient impeller at 1 Pa s. The Zwietering equation was found unsuitable for prediction of Njs at low Re.